Trading of used software licenses - Nisula, Katri (My University, 2017)
Software is often the biggest IT cost and one of the biggest IT assets for many companies. The software licenses are all the time a growing type of property. The need of cost efficiency has reached software assets as well and companies are eager to find solutions for the cost savings in this field of property. Selling forward additional and unnecessary software licenses can become to entrepreneur’s mind. Main question in this study is that how legislation relates to trading of used software licenses. Usually software is sold as licenses and the licensors want to keep themselves exclusive right such as copyright, right of reproduction and right of distribution. This study finds out, is it lawful to resell the software license or does licensor have the exclusive rights in every situation. The methodology in this study is legal dogmatics where legislation has an important role among legal literature and juridical practices. Intellectual property rights have an important impact beside European Union’s Directives. The legal situation is still uncertain, but Court of Justice in European Union possibly wanted to ensure the free movement of goods and parallel the legal practice between tangible and intangible assets in its decision C-128/11.
Keywords: software license; copyright; right of distribution; fi=Talousoikeus|en=Business Law|; fi=Talousoikeuden maisteriohjelma|en=Master's Programme in Business Law|